2020
DOI: 10.1016/j.addma.2020.101512
|View full text |Cite
|
Sign up to set email alerts
|

In situ radiographic and ex situ tomographic analysis of pore interactions during multilayer builds in laser powder bed fusion

Abstract: Porosity and high surface roughness can be detrimental to the mechanical performance of laser powder bed fusion (LPBF) additive manufactured components, potentially resulting in reduced component life. However, the link between powder layer thickness on pore formation and surface undulations in the LPBF parts remains unclear. In this paper, the influence of processing parameters on Ti-6Al-4V additive manufactured thin-wall components are investigated for multilayer builds, using a custom-built process replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 88 publications
(152 reference statements)
0
26
0
Order By: Relevance
“…They also suggested that the keyhole porosity regime varies slightly, which is also supported by a high fidelity simulation [ 158 ]. In contrast, Sinclair et al [ 160 ] revealed that the powder layer thickness alters the track height in LPBF, leading to inconsistent laser melting in subsequent build layers. They also revealed that keyhole pores can be removed via laser remelting.…”
Section: The Future? In Situ Imaging For Ultra-fast Solidification Processing Additive Manufacturingmentioning
confidence: 99%
See 2 more Smart Citations
“…They also suggested that the keyhole porosity regime varies slightly, which is also supported by a high fidelity simulation [ 158 ]. In contrast, Sinclair et al [ 160 ] revealed that the powder layer thickness alters the track height in LPBF, leading to inconsistent laser melting in subsequent build layers. They also revealed that keyhole pores can be removed via laser remelting.…”
Section: The Future? In Situ Imaging For Ultra-fast Solidification Processing Additive Manufacturingmentioning
confidence: 99%
“…In addition to the melt pool geometry studies, several recent studies focused on the fundamental origin of the keyhole dynamics and the evolution of keyhole porosity during LPBF in a single layer build [ 158 , 159 ] and multi-layer build conditions [ 153 , 160 ]. Cang et al [ 159 ] suggested that the keyhole porosity is increasingly sensitive to scan speed.…”
Section: The Future? In Situ Imaging For Ultra-fast Solidification Processing Additive Manufacturingmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen is expected to be present in both the virgin substrate and powder particles. During LPBF, the melt at the advancing solidification front can then become supersaturated with hydrogen, driving hydrogen diffusion from the melt into the bubble 28,30 and it is several orders faster than the diffusion of other atoms 53 .…”
Section: Keyhole-induced Bubble Lifetime Dynamics In Lpbfmentioning
confidence: 99%
“…For the laser powder bed fusion (LPBF) process, most defects are formed during the dynamic melting process, when the laser interacts with the solid and the melt pool [2,3]. The AM community distinguishes between lack of fusion pores, which are flat and irregular pores (voids) between non-fused powder layers, keyhole pores, which are irregular pores (voids) created by the laser and a high energy input, and gas pores, which are mostly spherical pores formed by adding gas to the melt pool [2,[4][5][6][7][8]. A detailed review of pores and voids created during the AM build process was recently published by Sola et al [2].…”
Section: Introductionmentioning
confidence: 99%